Mathematical Modeling of Temperature Field of Multilayer Enclosure Structures - Aksenov Boris; Karyakina Svetlana; Stepanov Oleg; Shapoval Anatoly; Bodrov Mikhail (MATEC Web of Conferences, 2016)
The mathematical model of heat exchange process through multilayer enclosure structure is constructed. Herein infiltration and heat-conducting inclusions are taken into account. Heat exchange process modeling in the stationary and non- stationary conditions is considered.The method of temperature field constructing based on the suggested model is offered. The three-dimensional boundary problem of non- stationary heat conductivity is solved numerically using the implicit method of alternating directions. The temperature field constructing of the enclosure structures in the non- stationary condition allows to track dynamics of thermal flows through enclosing structures and to receive the thermal resistance considering influence of heat-conducting inclusions.